Data integrity and security of digital signatures on electronic systems using the digital signature algorithm (DSA) - Saepulrohman, Asep; Ismangil, Agus (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
The digital signature generation process begins with the creation of a public key and a private key. A public key is generated and published to verify the signature and calculate the hash value of the received document. At present, in the very fast development of information technology, quantum computers have emerged the ability to solve very large and complex amounts of data calculated by qubits, which when compared to quantum computers can work 10 minutes to work on a process that takes 1025 years on a computer. Therefore, the research focuses on how electronic signatures on documents have a reliable security system. The Digital Signature Algorithm (DSA) is a key algorithm used for digital signatures, which uses the Secure Hash Algorithm (SHA-1) to convert messages into message digest and parameters based on the ElGamal signature algorithm. The author also shows an example of digital signature encryption and decryption process by taking any numbers p = 59419 and q = 3301 to prove that the message can be formed and verified its authenticity.